Dilemma Facing Patients Aged 75 Years and Older on Fluid Restriction When Drug Package Inserts Advise Use of a Lot of Water: A Cross-Sectional, Descriptive, and Hypothesis-Generating Study Using a Large Claims Database - Hiromi Koshizuka; Kenji Momo; Ayako Watanabe; Airi Matsuzaki; Yuka Kashiwabara; Katsumi Tanaka; Bengt Lindholm; Tadanori Sasaki (Adis, Springer Healthcare, 2023)
Abstract Background Several oral drugs are recommended to be taken with large amounts of water for reasons such as peptic ulcer prophylaxis. On the other hand, there are many patients with diseases that restrict water intake, and the actual frequency of patients receiving prescriptions in these conflicting situations is not clear. Objective Using a large claims database in Japan, this study aimed to determine the proportion of patients aged ≥ 75 years on fluid restriction who received drugs whose drug package insert mentioned "a large amount of water intake is needed when taking the drug". Methods We performed a prescription survey of older patients over 75 years of age using the Japan Medical Data Centre (JMDC) claims database. Out of approximately 8800 oral drugs used in Japan, we defined 29 drugs for which package inserts noted that a large amount of water intake is recommended during drug administration. We defined diagnosis codes for some common diseases for which restricted water intake is likely recommended: heart failure (NYHA class III or IV), liver cirrhosis with ascites, and chronic kidney disease stage 5, including dialysis patients. Results Of 5968 patients aged ≥ 75 years (men 47.7%), 320 (5.4%) patients with heart failure (2.8%, n = 170), liver cirrhosis (0.7%, n = 40), or chronic kidney disease (1.9%, n = 113), diagnoses likely associated with the need for fluid restriction, were prescribed drugs for which abundant fluid at intake was recommended. Among 29 identified drugs, 15 drugs were administered to older patients over 75 years with fluid restriction due to said diseases. Conclusions Of patients 75 years and older with disease likely requiring water restriction, 5.4% faced the dilemma of following advice to restrict fluid intake due to their diagnoses or to adhere to instructions in drug package inserts to have abundant fluid intake when taking the drug. Our study raises awareness regarding the dilemma of water restriction and intake in clinical settings, highlighting the importance of considering individual patient needs. These real-world findings emphasize the need for information and guidelines to assist healthcare professionals in navigating this dilemma and making informed decisions for the benefit of their patients.